EuroPsy: The Development of Standards for High-Quality Professional Education in Psychology - Lunt, I (2011)
The paper presents a brief history of the EuroPsy initiative which began in 1998 and is now in the process of implementation across European countries in the European Federation of Psychologists' Associations (EFPA). EuroPsy defines a standard of professional education that aims to promote a high quality of education and professional practice for psychologists. The initiative was substantially supported by developments within the European Union (EU) and more widely in Europe, in particular the so-called Bologna process. This process, however, had a major political focus with an explicit commitment to facilitate mobility. Concerns for quality and a high level of professional education and an implied focus on consumer or client protection may not always sit easily with a commitment to facilitating professional mobility. This paper presents some of the challenges and potential tensions inherent in the EuroPsy. © 2011 Hogrefe Publishing.